The feminine principle in the Sikh vision of the transcendent - Singh, Nikky-Guninder Kaur (Cambridge studies in religious traditions, 1993)
This work is a critical analysis of Sikh literature from a feminist perspective. It begins with Guru Nanak's vision of Transcendent Reality and concludes with the mystical journey of Rani Raj Kaur, the heroine of a modern Punjabi epic. The eight chapters of the book approach the Sikh vision of the Transcendent from historical, scriptural, symbolic, mythological, romantic, existential, ethical and mystical perspectives. Each of these discloses the centrality of the woman, and show convincingly that Sikh Gurus and poets did not want the feminine principle to serve merely as a figure of speech or literary device; it was intended rather to pervade the whole life of the Sikhs. The present work bolsters the claim that literary symbols should be translated into social and political realities, and in so doing puts a valuable feminist interpretation on a religious tradition which has remained relatively unexplored in scholarly literature.